2014
DOI: 10.1016/j.jecp.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial bootstrapping: Implicit binding of verbal working memory to visuospatial representations in children and adults

Abstract: When participants carry out visually presented digit serial recall, their performance is better if they are given the opportunity to encode extra visuospatial information at encoding-a phenomenon that has been termed visuospatial bootstrapping. This bootstrapping is the result of integration of information from different modality-specific short-term memory systems and visuospatial knowledge in long term memory, and it can be understood in the context of recent models of working memory that address multimodal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 24 publications
10
32
0
Order By: Relevance
“…Developmental trajectories in feature binding performance have previously been observed across children and into young adulthood using a range of tasks measuring within-domain visual and spatial binding (e.g., Brockmole & Logie, 2013;Cowan, Naveh-Benjamin, et al, 2006;Picard et al, 2012), verbal binding within sentences (Alloway et al, 2004;Kapikian & Briscoe, 2012), and across-domain binding between verbal and spatial information Darling et al, 2014). The present study extends this to a different task where visual and auditory-verbal materials were to be bound and held in working memory over short intervals.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Developmental trajectories in feature binding performance have previously been observed across children and into young adulthood using a range of tasks measuring within-domain visual and spatial binding (e.g., Brockmole & Logie, 2013;Cowan, Naveh-Benjamin, et al, 2006;Picard et al, 2012), verbal binding within sentences (Alloway et al, 2004;Kapikian & Briscoe, 2012), and across-domain binding between verbal and spatial information Darling et al, 2014). The present study extends this to a different task where visual and auditory-verbal materials were to be bound and held in working memory over short intervals.…”
Section: Discussionsupporting
confidence: 65%
“…For example, Cowan, Saults, and Morey (2006) found that memory for binding between visually presented names and locations improved between third grade (9-10 years), sixth grade (12-13 years) and adult participants, and also predicted performance on working memory span tasks. Taking a different approach, Darling et al (Darling, Parker, Goodall, Havelka, & Allen, 2014) observed that 6-year olds did not benefit from binding verbal-spatial information in working memory in digit recall, while 9-year olds and young adults did, suggesting a developmental shift in the ability to associate and utilize information from across domains.…”
mentioning
confidence: 99%
“…The experimental stimuli and procedure were modeled on the studies of (Allen et al, In press; Darling et al, 2012, 2014; Darling and Havelka, 2010). Sequences of six digits were created in which the digits 0–9 were randomly sampled without replacement.…”
Section: Experiments 2: Visuospatial Bootstrapping Effectmentioning
confidence: 99%
“…Specifically, when subjects are presented with sequences of digits in a spatial array, immediate verbal recall of these digits (akin to a digit span test) improves when digits are presented in a familiar visuospatial context (a typical keypad display) compared to an unfamiliar visuospatial context (an atypical keypad display; Allen et al, In press; Darling et al, 2012, 2014; Darling and Havelka, 2010). This ‘visuospatial bootstrapping effect’ is thought to reflect facilitated recall when verbal digit information can be linked to pre-existing visuospatial representations.…”
Section: Introductionmentioning
confidence: 99%
“…recall. The two random conditions have been used in some studies (Darling et al, 2012;Darling et al, 2014;Calia et al, 2015; and have never produced improved recall.…”
Section: Future Directions and Applicationsmentioning
confidence: 99%